Dampak Sikap terhadap Tuhan pada Kepuasan Hidup Mahasiswa Kristen di Jabodetabek pada Masa Pandemi - Yonathan Aditya (Konsorsium Psikologi Ilmiah Nusantara, 2021)
Having a positive attitude about God during suffering was known can maintain mental health. However, many people became disappointed in God during the pandemic. The purpose of this research was to study the attitude toward God among Christian students in the Jabodetabek area during pandemic. Multiple regression analysis was performed on data obtained from 369 Christian students (99 males and 270 females) and found that a negative attitude is a predictor of adverse life satisfaction while a positive attitude is a predictor for higher life satisfaction. A positive attitude decreased the association between negative attitude and life satisfaction. The result of this study implied that as long as the students maintain a high positive attitude toward God, the negative association of negative attitude toward life satisfaction can be controlled.